15th North American Caribou Workshop, 12-16 May 2014, Whitehorse, Canada - Åhman (editor in chief), Birgitta; Wiklund (technical editor), Eva; Hegel, Troy; Schmiegelow (issue editors), Fiona (Rangifer, 2015)
The 15th North American Caribou Workshop (NACW) was held from 12-16 May 2014, in the traditional territories of the Kwanlin Dün First Nation and the Ta’an Kwäch’än Council, in Whitehorse, Yukon, Canada. This biennial meeting is the largest technical conference of its kind dealing specifically with caribou biology and management. The first NACW was held in Whitehorse over three decades ago in 1983, and 13 subsequent workshops have been held across North America until now. With nearly 400 delegates from Canada, the United States, Norway, and Greenland attending the 2014 conference, it is evident that this “North American” gathering has truly become an international event. Furthermore, delegates attending this 15th NACW represented federal, provincial, territorial, state and First Nation governments, academia, non-governmental organizations, co-management boards and councils, private consultants, and industry, creating a relatively unique conference setting bringing together a variety of perspectives and concerns. The breadth of the participants in terms of geography, expertise and affiliation resulted in a rich base of human capacity to discuss issues related to caribou conservation and management.Given that it had been nearly three decades since the inception of this workshop, and with its return to the location of the first NACW, the organizing committee felt it was a fitting opportunity to look back and assess what had been achieved with respect to caribou conservation and management. As such, the theme of the 15th NACW was “Caribou Conservation and Management: What’s Working?” The opening session of the conference focussed on invited presentations explicitly addressing this question, and included topics on structured decision making, forest management, harvest monitoring, carnivore management, regional land use planning and management, and aboriginal perspectives on a long-term collaborative caribou recovery program in the southwest Yukon. We challenged our speakers to share what was working and why, and the information provided was valuable and timely, prompting many questions and discussion throughout the conference.